1996
DOI: 10.1126/science.274.5294.1830
|View full text |Cite
|
Sign up to set email alerts
|

Gibbons Warns of Decline in R&D

Abstract: This year's budget message from the White House to science agencies, delivered just before Thanksgiving, was a real turkey: Expect less in the 1998 fiscal year, which begins next October, than Congress appropriated this year. And the future holds more of the same, says Science Adviser Jack Gibbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 0 publications
1
47
0
Order By: Relevance
“…In recent years much effort has been expended towards fabricating long, flexible, high T c superconductor coated conductors with high critical current densities for electrical industry applications. One of the most successful approaches to date is the rolling assisted biaxially textured substrates (RABiTS) technique [1,2]. In this technique, biaxially textured Ni tapes are prepared by cold rolling and annealing, upon which high quality epitaxial oxide buffer layers and YBCO films can be grown.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years much effort has been expended towards fabricating long, flexible, high T c superconductor coated conductors with high critical current densities for electrical industry applications. One of the most successful approaches to date is the rolling assisted biaxially textured substrates (RABiTS) technique [1,2]. In this technique, biaxially textured Ni tapes are prepared by cold rolling and annealing, upon which high quality epitaxial oxide buffer layers and YBCO films can be grown.…”
Section: Introductionmentioning
confidence: 99%
“…This technique involves the formation of a crystallographic texture by cold rolling deformation and a subsequent recrystallization of the substrate at high temperatures. It has been shown that nickel tapes are well suited for the RABiTS approach [5]. Nickel forms a sharp {100} 001 cube texture after deformation and recrystallization at around 1000 • C. Nickel alloys (such as Ni-V, Ni-W, Ni-Cr or ternary alloys) are advantageous over pure nickel as the alloys show highly improved tensile strengths as well as strongly reduced ferromagnetism.…”
Section: Introductionmentioning
confidence: 99%
“…YBa 2 Cu 3 O 7−x (YBCO) coated conducting wires have attracted large interest in recent years because of their potential applications in the electric power industry [1][2][3][4][5]. To carry high critical current density (J c ), superconducting thin film must be well textured to minimize weak links at high-angle grain boundaries in the film [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been explored for the fabrication of biaxially textured templates on polycrystalline substrates [2,[10][11][12][13]. Ion-beam-assisted deposition (IBAD) has been successfully used to fabricate biaxially textured yttriastabilized zirconia (YSZ) films on polished metallic substrates [5,12,13]. The YSZ layer served as a template for epitaxial 3 Author to whom correspondence should be addressed: 9700 S. Cass Avenue, Argonne, IL 60439, USA.…”
Section: Introductionmentioning
confidence: 99%